An Analysis of Politeness Strategies Used by Female and Male Students in XI IIS Of SMA Bhaktiyasa Singaraja to Talk to Their Teachers Inside and Outside the Classroom - N W Sugitariani; I Ketut Seken; I Nyoman Pasek Hadisaputra (Lingua Scientia, 2016)
This study aimed to explain the types of politeness strategies used by female and male students of XI IIS of SMA Bhaktiyasa Singaraja to talk to their teachers inside and outside the classroom and the reason of using those strategies. The researcher was the key instrument in this study that collected the data by audio-recording the conversation between students and teachers, taking note of the phenomena and interviewing the subject of the study. The subjects of the study were the students in XI IIS of SMA Bhaktiyasa Singaraja who talked to their teachers. The politeness strategies used by students were analyzed based on Brown & Levinson’s theory of politeness. The result of this study showed that the strategies used by female and male students were bald on record politeness, positive politeness, and off record. Mostly, the students used impolite language which can be stated as pragmatic errors because the students’ motive was to get closer to the teachers so they used impolite language. It was different from the previous studies that indicated positive politeness strategy most used by speaker in formal situation. The result of this study indicated that the students used politeness strategies rarely even when they talked to their teachers in the classroom activities. The students’ reasons of using the impolite language most frequently than politeness strategies because they felt they were close with the teachers so that they used impolite language to show their friendliness.